PERAN KOMUNIKASI INTERPERSONAL DALAM MENDUKUNG KINERJA KARYAWAN PT. ADVANTAGE SCM CABANG SURAKARTA - Siswanta, Astri Handayani, Maya Sekar Wangi & (Transformasi, 2017)
This research was a descriptive-qualitative which try to describe the role of interpersonalcommunication which support the performance of employees in PT. Advantage SCM SurakartaBranch. By using the interactive analysis models belonging to the Sutopo (2006) , the resultsshowed that the interpersonal communications and diadik communications occurs in PT.Advantage SCM. The harmony of interpersonal communication and diadik communicationimpact on the result performance. Achievements of employees find it helpful with the presence ofmore intensive communication.Key words: Interpersonal Communication, Communication Performance And Loyalty